Safety and Feasibility of an Immersive Virtual Reality Intervention Program for Teaching Police Interaction Skills to Adolescents and Adults with Autism. Issue 8 (6th August 2020) - McCleery, Joseph P.; Zitter, Ashley; Solórzano, Rita; Turnacioglu, Sinan; Miller, Judith S.; Ravindran, Vijay; Parish‐Morris, Julia
Abstract : Low‐cost, wireless immersive virtual reality (VR) holds significant promise as a flexible and scalable intervention tool to help individuals with autism spectrum disorder (ASD) learn and develop critical practical life skills, including interacting safely and effectively with police officers. Previous research suggests that VR is a motivating intervention platform, but many individuals with ASD also exhibit anxiety and sensory sensitivities which might make it difficult to tolerate VR experiences. Here, we describe the results of a relatively large‐scale, National Institutes of Health‐funded systematic examination of the safety, feasibility, and usability of an immersive VR training program in adolescents and adults with ASD, aged 12 and older. Sixty verbally fluent individuals with no personal or immediate family history of seizures or migraines participated in either one ( n = 30) or three 45‐min ( n = 30) VR sessions using a lightweight wireless headset, and were monitored for side effects. Participants also reported on system usability, enjoyment, and willingness to engage in further VR sessions. Results confirm that immersive VR is safe, feasible, and highly usable for verbally fluent adolescents and adults with ASD. Lay Summary: Immersive virtual reality (VR) holds promise as a means to provide social skills interventions for individuals with autism spectrum disorder (ASD), but it is unclear whether associated anxiety and sensory symptoms might limit feasibility. Here, we report data that indicate that immersive VR is both safe and feasible for use in verbally fluent adolescents and adults with ASD, for up to three 45‐min sessions. Autism Res 2020, 13: 1418–1424 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc.